SYARIâAT ISLAM DAN UPAYA PEMBENTUKAN HUKUM POSITIF DI INDONESIA - Sularno, M (Islamic University of Indonesia, 2006)
The following article tries to investigate Islamic Shariâah and the positive law in Indonesia. Shariâah denotes the basic law that legislated by Allah and his prophet. All moslem should obey and apply Shariâah in all aspects of life. Departing from the opening of article 29 verse (1) of amended constitution 1945 and the theory interpretation of Hazairin concerning the article mentioned above that Islamic law constitutes the main reference and the the main sources of law legislation in Indonesia. Hence, to reach the above goal, it needs struggling of Indonesian moslem and the effort to reinterpret the doctrineof shariâah in accordance with the changing of situation and that of society. Kata kunci: syariâat, perjuangan, patuh, hukum positif dan undang-undang